THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION ON ANXIETY LEVELS IN 11th GRADE STUDENTS - Namira, Adinda; Karwati, Karwati; Somana, Aan (Journal of Advanced Nursing and Health Sciences, 2025)
Background: Anxiety is a psychological condition characterized by vague worries, accompanied by feelings of uncertainty, helplessness, isolation, and insecurity. Adolescents are a vulnerable group to anxiety, particularly due to academic pressures such as assignments, exams, and the demands of determining future educational directions. This study aims to determine the effect of progressive muscle relaxation therapy (PMR) on reducing anxiety levels among 11th grade students at State Islamic Senior High School Cimahi.Methods: The research used a pre-experimental method with a one-group pre-test and post-test design, involving 36 respondents who met the inclusion criteria. The instrument used to measure anxiety levels was the Hamilton Anxiety Rating Scale (HARS) questionnaire, administered before and after the intervention. The intervention consisted of PMR therapy conducted for three consecutive days. Data were analysed using the Shapiro-Wilk test for normality and the paired t-test to determine differences in anxiety scores before and after intervention.Results: The results showed a significant decrease in anxiety levels after the intervention; the mean score before was 20,81, which decreased to 10,39 after the intervention. The paired t-test yielded a p-value of 0,001 (< α = 0.05), indicating a significant effect of progressive muscle relaxation therapy in reducing anxiety.Conclusion: Therefore, this therapy can be considered a non-pharmacological alternative intervention to manage anxiety in adolescents.